2011
DOI: 10.1242/dev.066381
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption of aurora B uncovers an essential role for aurora C during early mammalian development

Abstract: SUMMARYMitosis is controlled by multiple kinases that drive cell cycle progression and prevent chromosome mis-segregation. Aurora kinase B interacts with survivin, borealin and incenp to form the chromosomal passenger complex (CPC), which is involved in the regulation of microtubule-kinetochore attachments and cytokinesis. Whereas genetic ablation of survivin, borealin or incenp results in early lethality at the morula stage, we show here that aurora B is dispensable for CPC function during early cell division… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
69
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(79 citation statements)
references
References 51 publications
(89 reference statements)
9
69
0
Order By: Relevance
“…1a). We were not able to obtain homozygous Aurkb lox-tet/lox-tet or Aurkb tet/tet mutants from crosses between heterozygous mice, in agreement with a lethal phenotype caused by the lack of Aurora B in embryos (34).…”
Section: Resultsmentioning
confidence: 74%
See 1 more Smart Citation
“…1a). We were not able to obtain homozygous Aurkb lox-tet/lox-tet or Aurkb tet/tet mutants from crosses between heterozygous mice, in agreement with a lethal phenotype caused by the lack of Aurora B in embryos (34).…”
Section: Resultsmentioning
confidence: 74%
“…Reducing Aurora B activity by means of RNA interference or small-molecule inhibitors results in failure in chromosome alignment and defective kinetochore-microtubule attachment, cleavage furrow formation, and cytokinesis, ultimately leading to tetraploidization (36)(37)(38)(39). Aurora B heterozygosity in the mouse results in increased tumor incidence, whereas complete loss of Aurkb prevents chromosome segregation and results in a premature mitotic exit (26,34).…”
Section: Discussionmentioning
confidence: 99%
“…To examine this idea further, we measured for changes, with respect to maternal age, in levels of 2 proteins: Mad2 and phosphorylated Aurora C (pAurora C). Aurora C is a substitute of Aurora B during meiosis, [34][35][36][37] and its active form pAurora C is thought to be involved in destabilizing erroneous KT-MT attachment, as such contributing to the fidelity of bivalent division. 34,[38][39][40] One further reason for examining Mad2 is that previous studies have shown that levels of this transcript, like those of other SAC components, are lower in oocytes of both aged mice and humans.…”
Section: C57bl6/j Oocytes Have Cohesion Loss But No Change In Sgo2 Wimentioning
confidence: 99%
“…Aurora-B or Aurora-C. On the other hand, given that Aurora-B and Aurora-C participate in the same CPC complex and are thought to play similar roles in mitosis (Fernández-Miranda et al 2011), their simultaneous inhibition has the advantage of preventing possible functional compensations. Inactivation of Aurora-A has been reported to induce the formation of either monopolar or multipolar spindles with microtubules of decreased mass and aberrant morphology, unable to align the condensed chromosomes on the metaphasic plate correctly.…”
Section: Figurementioning
confidence: 99%